The Effectiveness of Village Funds in Bridge Infrastructure Development: A Case Study in Sugihwaras Village - Firdha Irzatullaila; Dwiki Adi Putra; Doris Febriyanti (Universitas Muhammadiyah Palu, 2026)
This research is titled